Training in Germany - an investment to counter the skilled worker shortage : results of the 2017/18 BIBB Cost-Benefit Survey - Schönfeld, Gudrun [Verfasser]; Wenzelmann, Felix [Verfasser]; Pfeifer, Harald [Verfasser]; Risius, Paula [Verfasser]; Wehner, Caroline [Verfasser] (Bundesinstitut für Berufsbildung, 2020)
"Since a number of years, the German economy suffers from a lack of skilled workers in the labour market. Two of the most important options to cover the skill demand of firms are apprenticeship training and the recruitment of already trained workers from the external labour market. The costs of each of these options are important determinants for the choices made by firms. The Federal Institute of Vocational Education and Training examines the costs involved in each of the options based on a firm-level survey of 3,049 training firms and 996 non-training firms. This report informs about the apprenticeship training costs of the year 2017/2018 and the development of these costs over the past ten years. It further approximates the long-term benefits of apprenticeship training by calculating the firms' recruitment costs and by describing the retention behaviour. Overall, the analysis confirms that firms have strong financial incentives to cover their skill demand through the provision of training and the retention of the former apprentices." (authors' abstract; BIBB-Doku)
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; S 3.2 Unternehmen und Behörden; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; S 5.3 Personalentwicklung; Ausbildungsverhalten; Fachkräftebedarf; Berufsausbildung; Personalgewinnung; Kosten; Kosten-Nutzen-Analyse